(2^33+|2^33-3^22|)-3^22
Răspunsuri la întrebare
Răspuns de
4
(2^33+/2^33-3^22/)-3^22
2^33=(2^3)^11=8^11
3^22=(3^2)^11=9^11
8^11∠9^11→2^33∠3^22→ cantitatea din modul este negativă
↓
(2^33-2^33+3^22)-3^22=3^22-3^22=0
2^33=(2^3)^11=8^11
3^22=(3^2)^11=9^11
8^11∠9^11→2^33∠3^22→ cantitatea din modul este negativă
↓
(2^33-2^33+3^22)-3^22=3^22-3^22=0
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă